Electromagnetic Characteristics Analysis of the Interior Permanent Magnet Synchronous Motor considering Temperature Change - Jo, Byoung-Wook; Kang, Jun-Kyu; Song, Cheon-Ho; Kim, Ki-Chan (International Journal of Engineering and Technology, 2018)
Background/Objectives: Becauseofthe environmental pollution problem and the development of A rare earth magnet, research on IPMSM forElectric Vehicle(EV)s, which are eco-friendly automobiles, is actively under way. Methods/Statistical analysis: Inthis paper,the changes of electromagnetic field characteristics according to the temperature change of 20 , 80 , and 140 Â are compared and analyzed through Â Finite Element Method(FEM). Also, for the high efficiency design of the motor, through FEM we propose the ventilation hole design which reduces the temperature while keeping the output of the motor almost. Findings: As the result of FEM simulation, it was confirmed that the residual flux density increase and the winding resistance decrease due to the temperature decrease. Because of that, d-axis and q-axis inductance, and magnetic flux linkage are changed. In particular, it was confirmed that phase current and angle of phase current, which are the control parameters of IPMSM, is not accurately controlled unless temperature is taken into account. Also, at MTPA driving point the efficiency was improved according to temperature decrease, and at the field weakening point, the efficiency decreased as the temperature decreased. Finally, it was confirmed that the output can crease by drilling the ventilation hole considering the path of the magnetic flux through FEM simulation. Improvements/Applications: The study is most suitable for motors that require high power density. We plan to the study considering thermal analysis and electromagnetic field analysis at the same time. Â Â